Metagenomic Evaluation of Bacterial and Archaeal Diversity in the Geothermal Hot Springs of Manikaran, India - Bhatia, Sonu (Genome Announc, 2015)
Bacterial and archaeal diversity in geothermal spring water were investigated using 16S rRNA gene amplicon metagenomic sequencing. This revealed the dominance of Firmicutes, Aquificae, and the Deinococcus-Thermus group in this thermophilic environment. A number of sequences remained taxonomically unresolved, indicating the presence of potentially novel microbes in this unique habitat.